The Polio Communication Network Contribution to the Polio Outbreak Response in Ethiopia's Somali Region, 2013–2015. (1st January 2016) - Rozario, Shalini; Omer, Mohammed Diaaeldin; Gallagher, Kathleen; Aregay, Aron Kassahun; Shikh Aden, Bukhari; Mohamoud Abdi, Sahardid
Abstract : This article explores the Polio Communication Network's (PCN) contribution to the polio outbreak response in the Somali Region of Ethiopia from 2013 to 2015. The PCN strategies and innovations include the establishment of a communication network of experts, development of partnerships with locally trusted and influential groups, and capacity building of local structures. Results show PCN contribution through sustained high levels of community awareness of polio rounds and low rates of noncompliance with polio vaccination in line with the national indicator (< 1%). We argue that the context-sensitive approaches made significant gains in reaching traditionally missed, hard-to-reach, pastoral communities with polio information, improved communication capacity, and expertise, and contributed to the successful outbreak closure. The PCN experience in the Somali Region, one of Ethiopia's lowest-performing regions for health indicators, provides important communication lessons for the long term relevant to polio eradication and other public health programs. Due to the focus on building capacity in areas such as monitoring and data collection, generated social data demonstrated impact of communication approaches and has contributed to a better understanding of the behavioral and environmental factors affecting the demand for, and uptake of, health services in Ethiopia's Somali Region.